Conflict of interest policies and disclosure requirements among European Society of Cardiology national cardiovascular journals. Issue 7 (15th March 2012) - Alfonso, Fernando; Timmis, Adam; Pinto, Fausto J; Ambrosio, Giuseppe; Ector, Hugo; Kulakowski, Piotr; Vardas, Panos; ,; ,; Antoniades, Loizos; Ahmad, Mansoor; Apetrei, Eduard; et al.
Abstract : Disclosure of potential conflicts of interest (COI) is used by biomedical journals to guarantee credibility and transparency of the scientific process. COI disclosure, however, is not systematically nor consistently dealt with by journals. Recent joint editorial efforts paved the way towards the implementation of uniform vehicles for COI disclosure. This paper provides a comprehensive editorial perspective on classical COI-related issues. New insights into current COI policies and practices among European Society of Cardiology national cardiovascular journals, as derived from a cross-sectional survey using a standardised questionnaire, are discussed.